Reimagining Canada : language, culture, community and the Canadian constitution - Webber, Jeremy H. A., 1958- (McGill-Queen's University Press, 1994)
Webber begins by showing how different conceptions of culture, language, and nation shaped Canada's constitutional negotiations from 1960 until the referendum of 1992. He then calls for a reconception of the terms of the debate, claiming that the terms now used, often borrowed from quite different societies, have made resolution of the constitutional issues more difficult. He rejects the language of nation and nationalism, and the tendency towards exclusiveness implicit in that language, arguing for a Canadian community founded not on a rigid set of "shared values" but on shared debates and shared engagements through time. Recognizing that Canadians belong simultaneously to the larger community and to other more local communities each generating its own sense of allegiance Webber describes how their relationships are shaped by institutional, linguistic, and cultural factors and notes that these multiple influences produce an asymmetrical structure. He maintains that this structure should be reflected in an assymetrical constitution, and can be accommodated without undermining individual rights. Webber offers both an overview of the constitutional negotiations and a set of reflections on the appropriate relationship between culture, language, and political community in Canada. These reflections, while rooted in the Canadian context, hold lessons for other pluralistic federations, or for nations confronting similar issues of cultural accommodation.